Racial/ethnic differences in the prognostic utility of left ventricular mass index for incident cardiovascular disease. Issue 4 (17th April 2018) - Akintoye, Emmanuel; Mahmoud, Karim; Shokr, Mohamed; Sandio, Aubin; Mallikethi‐Reddy, Sagar; Sheikh, Muhammad; Adegbala, Oluwole; Egbe, Alexander; Briasoulis, Alexandros; Afonso, Luis
Abstract : Background: Evidence exists for racial/ethnic differences in left ventricular mass index (LVMI). How this translates to future cardiovascular disease (CVD) events is unknown. Hypothesis: The impact of racial/ethnic differences in LVMI on incident cardiovascular outcomes could have potential implications for the optimization of risk stratification strategies. Methods: Using the prospectively collected database of the Multi‐Ethnic Study of Atherosclerosis (MESA) involving 4 racial/ethnic groups (non‐Hispanic Whites, Chinese, Blacks, and Hispanics) free of CVD at baseline, we assessed for racial/ethnic differences in the relationship between LVMI and incident CVD using a Cox model. Results: 5004 participants (mean age, 62 ± 10 years; 48% male) were included in this study. After an average follow‐up of 10.2 years, 369 (7.4%) CVD events occurred. Significant racial/ethnic differences existed in the relationship between LVMI and incident CVD ( P for interaction = 0.04). Notably, the relationship was strongest for Chinese (HR per 10‐unit increase in LVMI: 1.7, 95% CI: 1.1–2.8) and Hispanics (HR per 10‐unit increase in LVMI: 1.9, 95% CI: 1.5–2.2). Non‐Hispanic Whites demonstrated the lowest relationship (HR: 1.3, 95% CI: 1.1–1.5). LVMI values of 36.9 g/m 2.7, 31.8 g/m 2.7, 39.9 g/m 2.7, and 41.7 g/m 2.7 were identified as optimal cutpoints for defining left ventricular hypertrophy (LVH) for non‐Hispanic Whites, Chinese, Blacks, and Hispanics, respectively. In secondary analysis of LVH (vs no LVH) using these optimal cutpoints, we found a similar pattern of association as above ( P for interaction = 0.04). For example, compared with those without LVH, Chinese with LVH had HR: 5.3, 95% CI: 1.6–17, whereas non‐Hispanic Whites with LVH had HR: 1.6, 95% CI: 1.2–2.1 for CVD events. Conclusions: Among 4 races/ethnicities studied, LVMI has more prognostic utility predicting future CVD events for Chinese and Hispanics and is least significant for non‐Hispanic Whites.